The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1017/s1121189x00000592
|View full text |Cite
|
Sign up to set email alerts
|

Is locating acute wards in the general hospital an essential element in psychiatric reform? The UK experience

Abstract: Locating psychiatric wards in general hospitals has long been seen in many countries as a key element in the reform of services to promote community integration of the mentally ill. In the UK, however, this is no longer a policy priority, and the recent trend has been towards small freestanding inpatient units, located either within the communities they serve, or on general hospital sites, but separate from the main building. Whether locating the psychiatric wards in the general hospital is essential to psychi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
8
0
1
Order By: Relevance
“…A related policy issue concerns how to provide acute beds in a humane and non-institutionalized way that is acceptable to patients, for example in general hospital units (Quirk & Lelliott, 2001; Tomov, 2001; Totman et al 2010; The ITHACA Study Group, 2011). For example, descriptive research in England has identified 131 services that are alternative to traditional acute in-patient settings.…”
Section: Resultsmentioning
confidence: 99%
“…A related policy issue concerns how to provide acute beds in a humane and non-institutionalized way that is acceptable to patients, for example in general hospital units (Quirk & Lelliott, 2001; Tomov, 2001; Totman et al 2010; The ITHACA Study Group, 2011). For example, descriptive research in England has identified 131 services that are alternative to traditional acute in-patient settings.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, they consider the resulting risk of a purely somatic view on the aetiology and treatment of mental disorders (…) to be much greater’ (Bücher, 2005). Along similar lines, Totman et al (2010, p. 285) argue that ‘where…the focus has shifted to a recovery model, establishing schizophrenia and other disorders as mental illnesses like any other may be seen as a less relevant and desirable goal, especially by professionals other than doctors’. These arguments relate to on an ongoing debate on whether a primarily biomedical image of psychiatric disorders is beneficial for persons with mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, this journal published an article discussing whether locating acute wards in the general hospital is an essential element in psychiatric reform (Totman et al 2010). Reviewing the pros and cons of in-patient psychiatric care at general hospitals, the authors mention a number of beneficial effects that have been anticipated when closing (or downsizing) large psychiatric hospitals and establishing psychiatric units at general hospitals: The provision of medical care for psychiatric patients, for example, as well as the accessibility and integration of psychiatric care into local communities are presumably better at the general hospital.…”
Section: Introductionmentioning
confidence: 99%
“…In the third editorial, Sonia Johnson and her collaborators (Totman et al, 2010) discuss the shift from general hospital-based psychiatry in the UK and the recent trend towards small freestanding inpatient units of no more than 4 or 5 wards, located in the communities they serve. Over the years, a divergence has emerged between England and other European countries over this issue and seems to have gone largely unnoticed in the academic literature.…”
mentioning
confidence: 99%
“…Nel terzo editoriale, Sonia Johnson e i suoi collaboratori (Totman et al, 2010) discutono della recente tendenza da parte della psichiatria britannica a spostare l'asse dell'assistenza per acuti dall'ospedale generale verso piccole unità autonome, dotate di non più di 4-5 posti letto, ubicate nel territorio. Sembra, in sostanza, essersi prodotta nel corso degli ultimi anni su questo aspetto una divergenza tra l'Inghilterra e gli altri Paesi europei e tale divergenza è stata largamente ignorata dalla letteratura scientifica.…”
unclassified